Tacrolimus dosage requirements in lung transplant recipients receiving antifungal prophylaxis with voriconazole followed by itraconazole: a preliminary prospective study. (8th July 2014) - Enderby, Cher Y.; Heckman, Michael G.; Thomas, Colleen S.; Keller, Cesar A.
Abstract Background Concomitant administration of the triazole antifungals, voriconazole or itraconazole, with tacrolimus can result in significant drug interaction in the transplant recipient. Limited published information exists regarding tacrolimus dosing when transitioning from voriconazole to itraconazole. The objective of this study was to evaluate the extent of the drug interaction with antifungal prophylaxis using voriconazole followed by a change to itraconazole in lung transplant recipients receiving tacrolimus. Methods This prospective study included lung transplant recipients receiving antifungal prophylaxis with voriconazole followed by a switch to itraconazole. Patients were followed from the time of transplant until two months after converting to itraconazole. All patients received standard immunosuppression with tacrolimus, mycophenolate mofetil, and a corticosteroid. Tacrolimus dose normalized concentrations using concentration/dose ratio were compared while receiving voriconazole versus itraconazole. Results Twenty lung transplant recipients were included in the final analysis. No difference was found with the tacrolimus dose normalized concentrations on voriconazole 254 ± 28 (ng/mL)/(mg/kg) compared with itraconazole 234 ± 34 (ng/mL)/(mg/kg), p = 0.65. Conclusion Tacrolimus dosage adjustments were not necessary when converting from voriconazole to itraconazole. Validation in a larger population is needed to confirm these findings.